1965
DOI: 10.1017/s0022172400044971
|View full text |Cite
|
Sign up to set email alerts
|

Elimination ofEperythrozoon coccoidesinfection from mouse colonies

Abstract: 1. Long-established infection of a mouse colony with Eperthyrozoon coccoides was eliminated by regular insecticidal treatments designed to reduce infestation with lice and fleas.2. Undesirable consequences of E. coccoides infection upon mice used as experimental animals are noted and an easy routine for exclusion of this parasite from mouse colonies is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Nevertheless, the presence of hemoplasma infection in the laboratory rats, suggests that hemoplasma infection is widespread in this animal species. It is particularly important to recognize that this potential confounding factor needs to be eliminated from colonies of rodents used in experimental studies [ 37 ]. Clinically silent infections are of major importance in research because they often go undetected until their presence is heralded by aberrations in experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the presence of hemoplasma infection in the laboratory rats, suggests that hemoplasma infection is widespread in this animal species. It is particularly important to recognize that this potential confounding factor needs to be eliminated from colonies of rodents used in experimental studies [ 37 ]. Clinically silent infections are of major importance in research because they often go undetected until their presence is heralded by aberrations in experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Derrick et al (1954) found E. coccoides survived up to 9 days in embryonated chicken eggs but attempts at passage were unsuccessful; serial passages in embryonated chicken eggs have been reported (Seamer, 1959) but not confirmed. The standard procedure for determining whether a mouse colony was infected was to splenectomize a dozen 3-to 4-month-old mice and examine their blood daily (Gledhill et al, 1965b). An indirect fluorescent-antibody test has been shown to be useful (Baker et al, 1971) and scanning electron microscopy has been suggested to be useful (Augsten, 1982) but a PCR assay would be preferred, especially for studies of latency.…”
mentioning
confidence: 99%